2013
DOI: 10.1177/0883073813508316
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Frontonasal Dysplasia Associated With Bilateral Periventricular Nodular Heterotopia

Abstract: Frontonasal dysplasia is an etiologically heterogeneous development alteration including a set of anomalies affecting the eyes, forehead, and nose as a result of a malformation of the frontonasal elevation. It could occur either in isolation or as part of a syndrome such as frontonasal dysplasia associated with periventricular heterotopia. Our goal is to document the first clinical case of prenatal diagnosis for frontonasal dysplasia associated with periventricular heterotopia by fetal magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Guion‐Almeida et al studied 21 patients with FND and identified a large number of neurologic problems: callosal agenesis (12 cases), basal encephalocele (10 cases), lipoma of the corpus callosum (four cases), and mental retardation (11 cases) 4 . Mental retardation and other neurological unfavorable outcomes (like motor dysfunction and epilepsy) are related to the presence of central nervous system abnormalities, which could affect up to 50% of the patients 3,7 . Additional studies such as fetal magnetic resonance imaging (MRI) could be helpful in diagnosing subtle findings otherwise unnoticed on US examination such as periventricular heterotopias 7 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Guion‐Almeida et al studied 21 patients with FND and identified a large number of neurologic problems: callosal agenesis (12 cases), basal encephalocele (10 cases), lipoma of the corpus callosum (four cases), and mental retardation (11 cases) 4 . Mental retardation and other neurological unfavorable outcomes (like motor dysfunction and epilepsy) are related to the presence of central nervous system abnormalities, which could affect up to 50% of the patients 3,7 . Additional studies such as fetal magnetic resonance imaging (MRI) could be helpful in diagnosing subtle findings otherwise unnoticed on US examination such as periventricular heterotopias 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Mental retardation and other neurological unfavorable outcomes (like motor dysfunction and epilepsy) are related to the presence of central nervous system abnormalities, which could affect up to 50% of the patients 3,7 . Additional studies such as fetal magnetic resonance imaging (MRI) could be helpful in diagnosing subtle findings otherwise unnoticed on US examination such as periventricular heterotopias 7 . These findings can be very helpful for prognosis and patient counseling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations